2022
DOI: 10.3390/cells11244057
|View full text |Cite
|
Sign up to set email alerts
|

MST4: A Potential Oncogene and Therapeutic Target in Breast Cancer

Abstract: The mammalian STE 20-like protein kinase 4 (MST4) gene is highly expressed in several cancer types, but little is known about the role of MST4 in breast cancer, and the function of MST4 during epithelial-mesenchymal transition (EMT) has not been fully elucidated. Here we report that overexpression of MST4 in breast cancer results in enhanced cell growth, migration, and invasion, whereas inhibition of MST4 expression significantly attenuates these properties. Further study shows that MST4 promotes EMT by activa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Recurrence after radical gastrectomy is the main obstacle to improve the overall survival of GC patients, but its molecular mechanism has not been well understood until now. MST4 promotes proliferation and migration of various cancer cells via different mechanisms [ 26 , 30 , 31 ]. Arora et al demonstrated that MST4 as a oncogene enhances cell growth and migration by promoting EMT via activating Akt in breast cancer [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recurrence after radical gastrectomy is the main obstacle to improve the overall survival of GC patients, but its molecular mechanism has not been well understood until now. MST4 promotes proliferation and migration of various cancer cells via different mechanisms [ 26 , 30 , 31 ]. Arora et al demonstrated that MST4 as a oncogene enhances cell growth and migration by promoting EMT via activating Akt in breast cancer [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…MST4 promotes proliferation and migration of various cancer cells via different mechanisms [ 26 , 30 , 31 ]. Arora et al demonstrated that MST4 as a oncogene enhances cell growth and migration by promoting EMT via activating Akt in breast cancer [ 26 ]. Moreover, MST4 directly phosphorylates β-catenin to promote the tumor cell proliferation and is associated with a poor prognosis of CRC [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…hepatocellular carcinoma, hepatocellular lipid droplets, MST3, MST4, nonalcoholic steatohepatitis, STE20-type kinases colorectal, prostate, and breast cancer as well as glioblastoma. [18][19][20][21][22][23][24][25][26] MST3 and MST4 are also implicated in the pathology of endothelial malformations, [27][28][29] in the regulation of neuronal function, [30][31][32] and in immune responses. 27,33,34 In this study, we focused on determining the relevance of STE20 kinases MST3 and MST4 in human HCC, and on investigating the possible synergies between these two proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, a low MST4 abundance has also been reported to associate with the progression of HCC and poor patient prognosis, and the functional inactivation of MST4 was found to increase proliferation, motility, and invasion of human HCC cells in vitro and to facilitate intrahepatic metastatic potential in vivo 16,17 . Notably, MST3 and MST4 have previously been described to control tumorigenesis in gastric, pancreatic, colorectal, prostate, and breast cancer as well as glioblastoma 18–26 . MST3 and MST4 are also implicated in the pathology of endothelial malformations, 27–29 in the regulation of neuronal function, 30–32 and in immune responses 27,33,34 …”
Section: Introductionmentioning
confidence: 99%